If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2b + 7) = 0 Reorder the terms: 4(7 + 2b) = 0 (7 * 4 + 2b * 4) = 0 (28 + 8b) = 0 Solving 28 + 8b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + 8b = 0 + -28 Combine like terms: 28 + -28 = 0 0 + 8b = 0 + -28 8b = 0 + -28 Combine like terms: 0 + -28 = -28 8b = -28 Divide each side by '8'. b = -3.5 Simplifying b = -3.5
| 3/4x2=5/4x+1/2 | | -5x-20=3x+12 | | 100=400-2.5t | | -6(3n-1)-2(1-6n)=-8n+6n | | 3(5x+8)-2(x+7)=36 | | 90-(5x-24)=c | | 6u-10=4u | | 8x+4=-2x+6 | | h(t)=1+20t-5t^2 | | 10x-15=-5x+60 | | 4(9+6k)= | | 175=400-2.5t | | 0.08(y-3)+0.02y=0.20y-0.3 | | c-2=-11 | | 2.6x+18=2.8x+22 | | 3m=5m-20 | | h(t)=-5x^2+20x-15 | | 4(x+2)-1=2x+2(4+x) | | 0.08(y-3)+0.20y=0.20y-0.3 | | 3=6(16) | | 4-3a/x | | 19=5-8m | | 3x^3-2x^2-12x-8=0 | | t+30+t+30/3+t+30/3-15 | | 7(-2-3c)= | | 3+y/2=6 | | -3.2=l+(.2) | | -39+7x=6(6x+8) | | 5x-4=6x-10 | | 26+x=385 | | 4(x+1)-20=4x-16 | | 7(-23c)= |